Diaspora Communication Patterns and Plurality of Tolerance in Barcelona, Spain - Ernanda Dalimunthe; Fitria Ayuningtyas (School of Communication Science and Media Business, 2024)
The Indonesian Diaspora includes all Indonesian people who are abroad. Diaspora and migration are phenomena that are often encountered in the history of nations in the world. Barcelona is a multicultural city with people of diverse backgrounds, a lot of Indonesians are interested in living there as a diaspora with several motivations. The education system, cultures, diversity, and inclusivity that Barcelona has to offer are tremendously accommodating, which can be translated as a good destination for Indonesian diasporas to pursue a better life. This research focuses on using Indonesian diasporas in Barcelona as the research subject, finding out the communication pattern they use daily, specifically within their tolerance level for minority groups. This research uses a qualitative method with a phenomenological approach to discover the adaptation process of each subject and how the changes in their level of tolerance affect their communication pattern and the approach to those whom they deem tolerable. From this research, the author concluded that the diasporas’ communication pattern has changed from a high-context culture which they used to implement in Indonesia to a low-context culture due to the multiculturalism and its daily adaptation in Barcelona by the citizens. This is indicated by the increase of their tolerance level because of the exposure to diverse groups in Barcelona which the diaspora learned from and adapted as part of their life.